PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN KONTRUKTIVISME PADA MATERI PERUBAHAN DAN PELESTARIAN LINGKUNGAN HIDUP UNTUK PEMBELAJARAN BIOLOGI KELAS X SMA - Putria Syabani; Darmawati Darmawati; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study was to produce a valid work sheet based on a constructivism approach on environmental change and environmental conservation materials for biology learning in grade x high school. This research was conducted at the Laboratory of Biology Education Department of PMIPA FKIP University of Riau and SMA Negeri 2 Bangko Pusako Kab. Rokan Hilir in September-December 2017. This type of research is a development research using the ADDIE model that is carried out until the development stage. There are 4 work sheet developed. The instruments of data collection in this research are work sheet assessment / validation sheets, and student response questionnaires. After work sheet was developed, validated by 4 validators then simulated on 15 students semester 5 of biology education FKIP UR, and the test is limited to 20 students of Class X in SMA Negeri 2 Bangko Pusako Kab. Rokan Hilir. The validation results show the average score of the design aspects of the 4 work sheet developed is 3.36 categories are very valid, the pedagogical aspect score is 3.40 categories are very valid, and the average score of content feasibility aspect is 3.20 valid categories. The average score of all aspects of work sheet is 3.40 categories is very valid. The simulation result shows 3.50 average score with very good category. The result of the limited trial shows the average score of 3.49 with very good category. The results of the answer analysis on the limited trial showed the average value of 84.25 (non experiment) with good category. The results of the answer analysis on the limited trial show the value of 83 (experiment) with good category. work sheet validation result based on contractivism approach on material change and environmental preservation in class X grade is valid and very goodKeywords: Development, LKPD, Constructivism, Changes And Conservation Of LivingEnvironment